Analysis of National Police Capacity Building Through Education and Training at The Central Sulawesi Regional Police Human Resources Bureau - Wahyono, Dwi; Nyoman Swedana; Ayu Annisa Sekarsari (LPPM STIE Mujahidin, 2023)
This study aims to determine the capacity building of the National Police in the Human Resources Bureau of the Central Sulawesi Regional Police, and to determine the development of individual, organizational and system capabilities in the Human Resources Bureau of the Central Sulawesi Regional Police. This type of research is qualitative, which produces descriptive data. Informants 4 people consisting of the Head of the Central Sulawesi Regional Police, Head of the Human Resources Bureau, Head of the Personal Sub-Division and Police Members who have attended basic education and training and career paths. Research results Development at the system level is less than optimal because the framework design related to policy settings and basic conditions that support the achievement of certain policy objectives, does not work as it should. Likewise, the formation of visionary leadership at the Polsek level, has become less than optimal in optimizing the management of operational areas both in the Intelkam technical function, Traffic technical function, Criminal Investigation technical function, Sabhara technical function, and Binmas technical function with organizational resources at the Palu Police Station. In turn, the goal of developing the capacity of members of the Police within the Palu Police Precinct in order to increase professionalism and organizational performance, especially maintaining Kamtibmas, is not yet optimal.